2020
DOI: 10.21203/rs.3.rs-32949/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Can Hyperperfusion of Nonaerated Lung Explain COVID-19 Hypoxia?

Abstract: Early stages of the novel coronavirus disease (COVID-19) have been associated with ‘silent hypoxia’ and poor oxygenation despite relatively small fractions of afflicted lung. Although it has been speculated that such paradoxical findings may be explained by impairment of hypoxic pulmonary vasoconstriction in infected lungs regions, no studies have confirmed this hypothesis nor determined whether such extreme degrees of perfusion redistribution are physiologically plausible. Here, we present a mathematical mode… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(57 reference statements)
0
7
0
1
Order By: Relevance
“…The hypoxic events in COVID-19 patients have been a mystery to medical caretakers and physicians. This is due to the fact that the patients display minimal visible distress, although clinical oxygen levels are remarkably low ( 99 ). Its presentation defies its pathophysiology, which initially led to its description of “Happy Hypoxia” ( 100 ).…”
Section: The Hypoxic Responsementioning
confidence: 99%
“…The hypoxic events in COVID-19 patients have been a mystery to medical caretakers and physicians. This is due to the fact that the patients display minimal visible distress, although clinical oxygen levels are remarkably low ( 99 ). Its presentation defies its pathophysiology, which initially led to its description of “Happy Hypoxia” ( 100 ).…”
Section: The Hypoxic Responsementioning
confidence: 99%
“…The presence of normal or high pulmonary blood flow in non-aerated lung areas is probably caused by the relative failure of the hypoxic pulmonary vasoconstriction mechanism in COVID-19 pneumonia [13,18]. Mathematical modeling has also confirmed that the amount of pulmonary shunt observed in patients with early stage severe COVID-19 is not plausible without hyperperfusion of the injured lung [19].…”
Section: Discussionmentioning
confidence: 94%
“…the fraction of lung affected in this way is often surprisingly low given the severity of the associated hypoxia and estimated shunt fractions (average 50%). If one assumes that ground-glass opacification represents lung that is nonventilated, these CT studies imply abnormally high ratios of shunt fraction to nonaerated lung fraction of 3.0 for COVID-19 compared to 1.3 for ARDS Herrmann et al, 2020. Their model finds that truly vast increases in diameter of pulmonary arterioles would be necessary to explain such a vast decrease in vascular resistance, opening of pulmonary vessels, and delivery of blood to non-aerated lung tissue, concluding only that 'Approximating vascular resistance using the Hagen-Poiseuille equation, this change in resistance corresponds to an increase in vascular diameter of 26 to 35%.…”
Section: Rush To Attribute Early Covid-19 Hypoxemia To Vascular Mecha...mentioning
confidence: 99%